Endothelin Receptor A Blockade Is an Ineffective Treatment for Adriamycin Nephropathy - Tan, Roderick J.; Zhou, Lili; Zhou, Dong; Lin, Lin; Liu, Youhua (PloS one, 2013)
Endothelin is a vasoconstricting peptide that plays a key role in vascular homeostasis, exerting its biologic effects via two receptors, the endothelin receptor A (ETA) and endothelin receptor B (ETB). Activation of ETA and ETB has opposing actions, in which hyperactive ETA is generally vasoconstrictive and pathologic. Selective ETA blockade has been shown to be beneficial in renal injuries such as diabetic nephropathy and can improve proteinuria. Atrasentan is a selective pharmacologic ETA blocker that preferentially inhibits ETA activation. In this study, we evaluated the efficacy of ETA blockade by atrasentan in ameliorating proteinuria and kidney injury in murine adriamycin nephropathy, a model of human focal segmental glomerulosclerosis. We found that ETA expression was unaltered during the course of adriamycin nephropathy. Whether initiated prior to injury in a prevention protocol (5 mg/kg/day, i.p.) or after injury onset in a therapeutic protocol (7 mg/kg or 20 mg/kg three times a week, i.p.), atrasentan did not significantly affect the initiation and progression of adriamycin-induced albuminuria (as measured by urinary albumin-to-creatinine ratios). Indices of glomerular damage were also not improved in atrasentan-treated groups, in either the prevention or therapeutic protocols. Atrasentan also failed to improve kidney function as determined by serum creatinine, histologic damage, and mRNA expression of numerous fibrosis-related genes such as collagen-I and TGF-β1. Therefore, we conclude that selective blockade of ETA by atrasentan has no effect on preventing or ameliorating proteinuria and kidney injury in adriamycin nephropathy.